Targeting the bacterial stringent response to combat human pathogens - Gąsior, Filip; Bryszkowska, Katarzyna; Klasa, Wiktoria; Potrykus, Katarzyna (Frontiers in Immunology, 2025)
In the era of increasing bacterial antibiotic resistance, finding new ways of combating pathogens is especially important. An attractive possibility is targeting bacterial survival strategies that microorganisms employ either to evade the host immune-responses or to adapt to the hostile environment encountered once inside the host. An example of the latter is the stringent response, mediated by guanosine penta- and tetra-phosphate, collectively referred to as (p)ppGpp. These molecules (alarmones) are responsible for switching bacterial gene expression and metabolism to allow survival under various stresses, such as nutritional deprivation and oxidative stress. (p)ppGpp turnover is mediated by various enzymes belonging to the RSH (RelA-SpoT homolog) family, some of which are capable of both, (p)ppGpp synthesis and hydrolysis, while others can perform only one of these functions. In this minireview, we discuss strategies that aim to disrupt or modulate the stringent response either by inhibiting these enzymes or on the contrary – enhancing their activities, as that goal can be achieved by several ways, i.e. blocking (p)ppGpp synthesis, inducing its synthesis or blocking its hydrolysis.